Emerging Roles for MicroRNAs in Diabetic Microvascular Disease: Novel Targets for Therapy - Zhang, Yu; Sun, Xinghui; Icli, Basak; Feinberg, Mark W. (Endocrine reviews, 2017)
Abstract Chronic, low-grade systemic inflammation and impaired microvascular function are critical hallmarks in the development of insulin resistance. Accordingly, insulin resistance is a major risk factor for type 2 diabetes and cardiovascular disease. Accumulating studies demonstrate that restoration of impaired function of the diabetic macro- and microvasculature may ameliorate a range of cardiovascular disease states and diabetes-associated complications. In this review, we focus on the emerging role of microRNAs (miRNAs), noncoding RNAs that fine-tune target gene expression and signaling pathways, in insulin-responsive tissues and cell types important for maintaining optimal vascular homeostasis and preventing the sequelae of diabetes-induced end organ injury. We highlight current pathophysiological paradigms of miRNAs and their targets involved in regulating the diabetic microvasculature in a range of diabetes-associated complications such as retinopathy, nephropathy, wound healing, and myocardial injury. We provide an update of the potential use of circulating miRNAs diagnostically in type I or type II diabetes. Finally, we discuss emerging delivery platforms for manipulating miRNA expression or function as the next frontier in therapeutic intervention to improve diabetes-associated microvascular dysfunction and its attendant clinical consequences.